Unhelmeted Injured Cyclists in a Canadian Emergency Department: Cycling Behavior and Attitudes Towards Helmet Use. (19th March 2022) - Varriano, Brenda; Porplycia, Danielle; Friedman, Steven Marc
Introduction: We seek to characterize unhelmeted injured cyclists presenting to the emergency department: demographics, cycling behavior, and attitudes towards cycling safety and helmet use. Methods: This was a prospective case series in a downtown teaching hospital. Injured cyclists presenting to the emergency department were recruited for a standardized survey if not wearing a helmet at time of injury and over age 18. Exclusion criteria included inability to consent (language barrier, cognitive impairment) or admission to hospital. Results: We surveyed 72 UICs (unhelmeted injured cyclists) with mean age of 34.3 years (range 18–68, median 30, IQR 15.8 years). Most UICs cycled daily or most days per week in non-winter months (88.9%, n = 64). Most regarded cycling in Toronto as somewhat dangerous (44.4%, n = 32) or very dangerous (5.9%, n = 4). Almost all (98.6%, n = 71) had planned to cycle when departing home that day. UICs reported rarely (11.1%, n = 8) or never (65.3%, n = 47) wearing a helmet. Reported factors discouraging helmet use included inconvenience (31.9%, n = 23) and lack of ownership (33.3%, n = 24), but few characterized helmets as unnecessary (11.1%, n = 7) or ineffective (1.4%, n = 1). Conclusions: Unhelmeted injured cyclists were frequent commuter cyclists who generally do not regard cycling as safe yet choose not to wear helmets for reasons largely related to convenience and comfort. Initiatives to increase helmet use should address these perceived barriers, and further explore cyclist perception regarding risk of injury and death.